Does negative contact undermine attempts to improve intergroup relations? Deepening the understanding of negative contact and its consequences for intergroup contact research and interventions. (2nd March 2021) - Schäfer, Sarina J.; Kauff, Mathias; Prati, Francesca; Kros, Mathijs; Lang, Timothy; Christ, Oliver
Abstract: Intergroup contact is an established pathway to improve intergroup relations. Research has long focused on mainly positive intergroup contact and its capability to improve intergroup relations. Yet, if members of different groups meet, they will not only make positive, but possibly also negative intergroup contact experiences. Recent research considering both positive as well as negative intergroup contact has raised concerns about potentially stronger effects of negative compared to positive contact. These new insights and the increasing awareness of potentially detrimental effects of contact could lead to doubts about whether it is always sensible to bring individuals from different groups together. Our article first updates the latest review on joint effects of positive and negative intergroup contact. We find that there is no clear tendency for either positive or negative intergroup contact to yield stronger effects on intergroup relations, and we portray factors that might influence these effects. Such factors—for example an individual's prior experiences—could play a crucial role in defining the relevance of negative contact in everyday settings. We continue by answering calls to increase a more qualitative understanding of what kinds of experiences are seen to be intergroup contact, and where intergroup contact in everyday life is experienced from a lay understanding, with new qualitative data from British White and British Asian individuals. Our results demonstrate that positive as well as negative contact is often rather casual and happens in public spaces and at work. Interventions explicitly addressing these spaces may help to reach more people. We also demonstrate that positive contact is much more frequent than negative contact. This finding is confirmed in the third section, which reviews the relative frequency of positive and negative intergroup contact. Last but not least, we discuss the implications of our review for practitioners and researchers alike.